2018
DOI: 10.1016/j.jinf.2017.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of patients with Streptococcus suis infection in Viet Nam: A case-control study

Abstract: HightlightsSevere hearing and vestibular impairment persists in many S. suis survivors.Hearing function tends to only improve in the first 3 months post discharge.Vestibular dysfunction shows little recovery during the follow-up time period.Survivors reported significantly lower health status and quality of life.Appropriate patient management strategies are needed to reduce disease impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…De hecho, este agente es el más frecuente en casos de meningitis bacteriana aguda en algunos países del sudeste asiático 3 . Es de interés también destacar la hipoglucorraquia extrema y la alta tasa de secuelas auditivas asociadas a esta especie, y cuya frecuencia se reduce con el uso de corticoesteroides, aunque en este caso no demostró tener impacto 3,4 .…”
Section: Discussionunclassified
“…De hecho, este agente es el más frecuente en casos de meningitis bacteriana aguda en algunos países del sudeste asiático 3 . Es de interés también destacar la hipoglucorraquia extrema y la alta tasa de secuelas auditivas asociadas a esta especie, y cuya frecuencia se reduce con el uso de corticoesteroides, aunque en este caso no demostró tener impacto 3,4 .…”
Section: Discussionunclassified
“…Data on mortality and disability were obtained through a systematic literature review 2 and a prospective follow-up study of patients with laboratory-confirmed S. suis infection admitted to the National Hospital for Tropical Diseases (NHTD) in Hanoi, Viet Nam between November 2014 and October 2015. 10…”
Section: Methodsmentioning
confidence: 99%
“…2 However, we also checked how the burden estimates vary if applying a smaller CFR of 4%, the pooled estimate for studies with meningitis patients. In the follow-up study, all cases with severe hearing loss showed vestibular dysfunction, 10 therefore we did not consider the impact of severe hearing loss without vestibular dysfunction in S. suis survivors. Hearing loss was defined based on audiometry, which measured the average of hearing thresholds over four frequencies (0.5, 1, 2 and 4 kHz) in the better ear.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations